دراسة استقصائية وبيوكيميائية لنباتات تستعمل كبديل مرافق اثناءالعالج الكيميائي ضد السرطان. - بن هارون فاطمة الزهرة (University of Eloued جامعة الوادي, 2024)
In order to value the contribution of certain medicinal plants used by cancer patients, we conducted a morphological and biochemical study on two such plants. Our study began with a field survey of the medicinal plants used by 50 cancers patients. From this survey, we selected two plants : Atriplex halimus L. and Rheum palmatum, due to the limited number of studies on them. To achieve the study goal, we conducted several chemical tests to identify the secondary metabolites present in the two plants. which resulted in the detection that the Atriplex h plant contains flavonoids, catechins, phenolic compounds, saponins, and alkaloids, and does not contain volatile oils and glycosides. Plant Rheum palmatum contains glycosides, saponins, phenolic compounds, flavonoids, gallic tannins, and volatile oils. It does not contain alkaloids and catechins. The majority stated that the boiling method is their preferred method For the biological part, we investigated the biological activity of the plant extracts on two types of bacteria, Escherichia coli and Staphylococcus aureus. We observed an inhibitory effect on the Escherichia coli bacterial strain for Atriplex h, recording the highest average inhibitory diameter of 24 mm and the lowest of 10 mm. In contrast, Rheum p showed an inhibitory diameter of 11mm. For the Staphylococcus a bacterial strain, no inhibitory diameter was recorded for Atriplex h, while Rheum p recorded the highest average inhibitory diameter of 19 mm and the lowest of 10 mm. The antioxidant activity of the ethanol extracts of the two plants was evaluated using the DPPH (2.2-diphényl-1-picrylhydrazyl) assay, yielding the best numerical result.
تنوع حيوي وفيزيولوجيا النبات
Keywords: cancer; survey; biological activity; antioxidant activity; Atriplex halimus L.; Rheum